Transient Vestibulopathy in Wallenberg’s Syndrome: Pathologic Analysis - Kattah, Jorge C.; Saber Tehrani, Ali S.; Roeber, Sigrun; Gujrati, Meena; Bach, Sarah E.; Newman Toker, David E.; Blitz, Ari M.; Horn, Anja K. E. (Frontiers in Neurology, 2017)
Objective: To report an unusual lateral medullary stroke (LMS) associated with transient unidirectional horizontal, nystagmus and decreased horizontal vestibulo-ocular reflex (h-VOR) gain that mimicked a peripheral vestibulopathy. MRI suggested involvement of caudal medial vestibular nucleus (MVN), however, the rapid resolution of the nystagmus and improved h-VOR gain favored transient ischemia without infarction. Decreased h-VOR gain is expected with peripheral vestibular lesions within the labyrinth or superior vestibular nerve; less frequently lateral pontine strokes involving the vestibular root entry, the vestibular fascicle or neurons within the MVN may be responsible. The h-VOR is typically normal in LMS. Methods: Clinico- pathologic examination of a 61 year-old man with an acute vestibular syndrome (AVS) and left LMS who died 3 weeks after the stroke. Post-mortem brainstem analysis was performed. Results: The stroke involved the lateral medulla and ponto-medullary junction, near the MVN, sparing the cerebellum and pons. To explain transient vestibular findings there are two possible hypotheses; the first would be that the MVN survived the ischemic process and would be histologically intact and the second that vestibular afferents in the horizontal semicircular canal were ischemic and recovered after the ischemic process. Neuropathological examination showed a left LMS whose extent matched that seen by imaging. Non-ocular motor signs correlated well with structures affected by the infarction. Neurons and glia within nearby MVN were spared, as predicted by the rapid normalization of the ocular motor signs. Although unlikely, the possibility of intralabyrinthine arteriolar ischemia cannot be excluded. Additionally, truncal lateropulsion was due to combined lateral vestibulospinal tract and lateral reticular nucleus infarction. Conclusion: LMS may rarely be associated with an AVS that either represents or mimics a peripheral vestibulopathy. To our knowledge this is the first neuropathologic examination of the brainstem of a LMS associated with transient vestibular findings.